Self-Efficacy and Depression in Boxers: A Mediation Model - Chen, Xin; Qiu, Nan; Chen, Chao; Wang, Dexin; Zhang, Guodong; Zhai, Liang (Frontiers in Psychiatry, 2020)
Background Depression has become one of the most common problems faced by athletes. In many mental health problems, its production and development mechanisms and influencing factors have received full attention from researchers, whereas boxers’ depression has received limited attention. This study explored the relationship between boxers’ self-efficacy and depression, as well as the effect of self-control as a mediating factor. Methods This study used the athlete self-efficacy scale (ASES), the self-control scale (SCS), and the Center for Epidemiologic Studies depression scale (CES-D). Using a large number of randomly selected samples, a total of N=231 boxers (age: M =20.28, SD = 2.60, ages around 18 to 32; the total number of years of exercise: M = 6.07 years, SD = 2.90, years around 1 to 15; 144 male) of Chinese national athletes participated the study. Results Self-efficacy and self-control were negatively correlated with depression; self-efficacy was positively correlated with self-control. In addition, self-control played a partial mediation role between self-efficacy and depression among boxers. Conclusion Above all, an important way to improve and prevent the depression of Chinese boxers maybe enhance their level of self-efficacy and self-control.